Combined tetrahydrocannabinol and cannabidiol to treat pain in epidermolysis bullosa: a report of three cases. (14th November 2018) - Schräder, N.H.B.; Duipmans, J.C.; Molenbuur, B.; Wolff, A.P.; Jonkman, M.F.
Summary: Epidermolysis bullosa (EB) is a genetic blistering disorder characterized by intense pain related to disease pathology and care‐based interventions. Opioid‐based therapies underpin pain care in EB; however, they are unable to provide adequate analgesia in a significant proportion of patients. Cannabinoid‐based medicines (CBMs) have been studied increasingly for pain conditions of various aetiologies and pose as a novel dimension for pain care in EB. We present three patients with EB who were prescribed pharmaceutical‐grade sublingually administered CBMs comprising tetrahydrocannabinol and cannabidiol. All three patients reported improved pain scores, reduced pruritus and reduction in overall analgesic drug intake. Abstract : What's already known about this topic? Pain is the most burdening symptom for patients suffering from severe epidermolysis bullosa (EB). Patients are exposed to numerous drug interventions, including high‐dose strong opioids, which often do not provide adequate analgesia and may induce adverse effects. Cannabinoid‐based medicines (CBMs) have been investigated for pain of various aetiologies and show promise through their interaction with the endocannabinoid system localized to central pain circuits. Cannabidiol has been reported to reduce wound pain in children with EB. What does this study add? The prescription of sublingually administered pharmaceutical‐grade CBMs may add additional value to pain‐care in EB and should be further investigated. Linked Comment: Martinez. Br J Dermatol 2019; 180 :711–712 . Plain language summary available online